Branched Chain In Situ Hybridization for Albumin as a Marker of Hepatocellular Differentiation. (January 2015) - Shahid, Mohammad; Mubeen, Aysha; Tse, Julie; Kakar, Sanjay; Bateman, Adrian C.; Borger, Darrell; Rivera, Miguel N.; Ting, David T.; Deshpande, Vikram
<x xml:space="preserve">Abstract</x> Albumin, widely recognized as a highly sensitive and specific marker of hepatocellular carcinoma (HCC), is currently unavailable in the diagnostic laboratory because of the lack of a robust platform. In a prior study we detected albumin mRNA in the majority of intrahepatic cholangiocarcinomas using a novel branched chain RNA in situ hybridization (ISH) platform. We now explore the utility of albumin ISH as a marker of hepatocellular differentiation in HCCs, and compare its sensitivity with Hep Par 1 and Arginase-1. We evaluated 93 HCCs and its mimics including neuroendocrine tumors of the gastrointestinal tract (n=31), neuroendocrine tumors of the pancreas (n=163), melanoma (n=15), and gallbladder carcinoma (n=34). We performed ISH for albumin and immunohistochemistry for Hep Par 1 and Arginase-1. Five previously uncharacterized hepatic neoplasms from our files were also evaluated. Immunohistochemistry for Arginase-1 was performed on 59 intrahepatic cholangiocarcinomas. In addition, 43 HCCs evaluated on the manual platform were also examined on the automated instrument. Fifty-five percent of HCCs were moderately differentiated and 39% poorly differentiated. The sensitivity of ISH for albumin was 99%, with 92 of 93 HCCs staining positive for albumin. In contrast to ISH, the sensitivity of immunohistochemistry for Hep Par 1 and Arginase-1 was 84% and 83%, respectively. The sensitivity of albumin for poorly differentiated HCCs was 99%, whereas that for Arginase-1 and Hep Par 1 was 71% and 64%, respectively. Ninety-seven percent of the HCCs showed albumin positivity in >50% of tumor cells using the ISH platform, as compared with 76% and 70% for Hep Par 1 and Arginase-1 immunohistochemistry, respectively. Three of the 5 previously uncharacterized neoplasms were positive for albumin ISH. Automated albumin ISH platform performed equivalently to the manual format, with albumin reactivity in >50% of tumor cells in all 43 cases that were tested on both platforms. All non-HCCs were negative for albumin. All 59 intrahepatic cholangiocarcinomas were negative for Arginase-1. In conclusion, branched chain ISH performed on manual and automated mode is a robust assay for detecting albumin with sensitivity for poorly differentiated HCCs superior to Arginase-1 and Hep Par 1. When interpreted in conjunction with Arginase-1, albumin ISH offers a high level of sensitivity and specificity.